2011
DOI: 10.1017/s0022149x10000921
|View full text |Cite
|
Sign up to set email alerts
|

Endoparasite fauna of five Gadiformes fish species from the coast of Chile: host ecology versus phylogeny

Abstract: The aims of the present study were to compare, using multivariate analyses, the degree of similarity of the endoparasite fauna of five fish species belonging to the order Gadiformes: Merluccius gayi, Merluccius australis, Macruronus magellanicus (Gadoidei) and Micromesistius australis and Nezumia pulchella (Macrouroidei), from the southern and central Chilean coast, and to evaluate whether the composition of the endoparasite fauna was determined by phylogenetic or ecological relationships. We employed our data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 27 publications
0
22
1
Order By: Relevance
“…The composition of the endo-parasite fauna of a host is dependent upon the host's feeding and other habits as well as host-specificity and distribution of the parasite [12]. In the present study, Cichlidae, Oreochromis urolepis harboured metacercariae, strigeids in the eyes and acanthocephala, in the intestine.…”
Section: Parasite Communitiesmentioning
confidence: 48%
“…The composition of the endo-parasite fauna of a host is dependent upon the host's feeding and other habits as well as host-specificity and distribution of the parasite [12]. In the present study, Cichlidae, Oreochromis urolepis harboured metacercariae, strigeids in the eyes and acanthocephala, in the intestine.…”
Section: Parasite Communitiesmentioning
confidence: 48%
“…Moreover, Chávez et al (2012) (Froese and Pauly, 2015), in line with Klimpel et al (2006), who demonstrated that parasite diversity was higher for demersal deep-sea fish than for bathypelagic species.…”
Section: Exploring Phylogenetic and Ecological Relationshipsmentioning
confidence: 58%
“…Numerous studies have evaluated the importance of ecological factors (i.e., diet, depth, habitat, etc.) as driving forces of the community structure of fish parasites (e.g., González et al, 2001;Muñoz, 2006;Mateu et al, 2014;Constenla et al, 2015), but research exploring the links between ecology and phylogeny in determining parasite richness are scarce (e.g., Poulin & Rohde, 1997;Morand et al, 2000;Muñoz et al, 2006;Chávez et al, 2012).…”
Section: Exploring Phylogenetic and Ecological Relationshipsmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have explored how the ecology and phylogeny of marine fishes influences the similarity of their parasite communities. Support for the role of host phylogeny has been variable, ranging from substantial to absent when compared to factors such as spatial or ecological overlap among host species (Cribb et al 2002, Muñoz et al 2007, Vignon and Sasal 2010, Chávez et al 2012). However, these studies were conducted at different scales (individual host, host population, host species) and employed a variety of measures of similarity of communities in which certain larval parasites were lumped into morphospecies or excluded.…”
Section: Discussionmentioning
confidence: 99%